High capacity and miniaturized flexible chipless RFID tag using modified complementary split ring resonator - Jalil, Mohd Ezwan; A. Rahim, Mohamad Kamal; Mohamed, Himdi; Samsuri, Noor Asmawati; Murad, Noor Asniza; Dewan, Raimi; A. Majid, Huda; Mohamed Nafis, Nur Biha; Nur, Levy Olivia; Nugroho, Bambang Setia (2021)
This paper aims to produce a high data capacity and miniaturized flexible chipless RFID tag based on the frequency signature using the Modified Complementary Split Ring Resonator (MCSRR). The proposed 19 bits chipless RFID tag using the frequency shifting technique consists of five slotted overlaying MCSRR with Different Width (MCSRR with DW) structures and the dimension of 48 mm x 48 mm. The structure is designed by using a flexible (Polyethylene Terephthalate ) PET substrate with permittivity of 0.2. The operating frequency is between 0.9 GHz and 2.7 GHz. The advancement of slotted overlaying MCSRR with DW structures has successfully miniaturized the chipless RFID tag structure to about 107 mm2/ bit, 0.02/2 mid =bit and 0.09 GHz/bit by maximizing the number of resonators in a limited space and minimizing the frequency separation between the resonators. The omnidirectional tag antenna is incorporated with the proposed MCSRR structure using the retransmission measurement method. The log-periodic antenna with a gain of 5-7 dBi is used for this measurement to improve the range distance between tag and reader system. Based on the retransmission measurement involving the antenna tag, the 19 bits chipless RFID tag which consists of five MCSRR with DW structures can be detected with a maximum range distance of 30 cm and a power transmitted level of 30 dBm.